Calculation of Lindemann's melting Temperature and' Eutectic Point of bcc Binary Alloys - Hung, Nguyen Van; Toan, Nguyen Cong; Giang, Hoang Thi Khanh (VNU Journal of Science: Mathematics - Physics, 2010)
Abstract